Geochronology of a Paleoproterozoic metamorphic complex in the Shuangsheng area of Inner Mongolia: constraints on crustal evolution. Issue 10 (31st May 2023) - Cheng, Qian; Lu, Lu; Wang, Yan; Fu, Junyu; Guo, Rongrong; Zhong, Hui; Yang, Xiaoping; Du, Jiyu
ABSTRACT: The Central Asian Orogenic Belt (CAOB) contains many microblocks, and their Precambrian basement origin and crustal evolution are disputed. This study focuses on the geochronology of metamorphic complexes from the Shuangsheng area, southeastern Inner Mongolia. Combined with regional geological data, we discuss the tectonic attribution of the metamorphic complexes and provide geochronological evidence for regional crustal evolution and tectonic affinity. From the Shuangsheng area, the Pingandi metamorphic complex and Baolige metamorphic complex are composed of greenschist–amphibolite facies metamorphic intrusive rocks and metamorphic supracrustal rocks, mainly including tremolite rock, chlorite rock, actinolitite (gneissic) plagioamphibolite, actinolitite schist, marble, and feldspar quartzite. Zircon U-Pb geochronology analysis of actinolitite and plagioamphibolite suggests that there were two intermediate-acid magmatic events (2500–2400 Ma and 2050–1980 Ma), one basic magmatic event (1860 Ma), and three metamorphic events (1930–1890 Ma, 1815–1785 Ma and 1740–1730 Ma). Based on comparisons with the regional Precambrian chronological spectrum, geotectonically, Precambrian geological records from the Shuangsheng area should belong to the basement of the Bainaimiao Arc Terrane (BAT). Each segment of the BAT shows consistent Precambrian chronological frameworks, which indicates that the BAT has a unitive Precambrian basement. The basement underwent crustal growth during 3.0–2.4 Ga and 2.1–1.4 Ga and multistage crustal reconstruction between 2.75 and 0.55 Ga, which is different from the crustal evolution of the North China Craton, northeast Gondwana continent, and Tarim Craton. In the early Palaeozoic, the Precambrian material provided varying source contributions to the arc crust of the BAT through crust–mantle interaction. Graphical Abstract: uf0001